The Urgency of Reforming Consumer Protection Law in Encountering to the Digital Business Ecosystem in Indonesia - Agus Panahatan Panjaitan; Suartini; Aris Macmud (Journal of Law, Politic and Humanities, 2026)
The digitalization of business in Indonesia has brought significant changes to transaction patterns and consumer–business relationships. However, this rapid growth has also raised several new consumer protection issues, including online fraud, violations of privacy rights, and unclear legal responsibilities for digital businesses. This study aims to analyze the importance of consumer protection in Indonesia’s digital business landscape and identify issues and solutions to strengthen it. The research method applied is the normative juridical method through case studies, a review of related literature, and an examination of statutory regulations. The findings reveal that current consumer protection frameworks, such as the Law on Electronic Information and Transactions and Law Number 8 of 1999 on Consumer Protection, still contain many gaps in adapting to the evolving dynamics of online transactions. Regulatory reforms and the enhancement of consumer digital literacy are required to ensure legal protection is more effective and responsive to technological developments. In conclusion, collaboration among the government, businesses, and society is urgently needed to strengthen consumer protection in the digital era and to create a safe and equitable digital business environment.